Salivary cortisol and α-amylase levels following admission to paediatric intensive care. (29th September 2015) - Gonzalez, MDP; Als, L; 'Donnell, KOÂ; Glover, V; Nadel, S; Cooper, M; Pierce, C; Hau, S; Kramer, T; Garralda, E
Abstract : Background: The hypothalamus-pituitary-adrenal (HPA) and sympathetic-adrenal-medullary (SAM) axes play an important role in the stress responses of children with critical illness admitted to a paediatric intensive care unit (PICU). While lower levels of plasma cortisol during admission for meningococcal disease have been associated with higher mortality, it is not known whether critical illness affects the subsequent regulation of these stress response-mediating mechanisms, and whether any dysregulation is related to psychological sequelae. Aims: The present investigation aims to assess whether HPA and SAM axis function, as measured by salivary cortisol and α-amylase (sAA)—two non-invasive markers of the activation of the HPA and SAM axis, respectively—is altered 3 to 6 months following critical illness and PICU admission. Methods: The study is part of a prospective study of neuropsychological function in children following admission to PICU. Salivary cortisol and sAA levels of children aged 5 to 16 admitted to PICUs were documented 3–6 months following discharge, and compared as a whole group and as disorder subgroups (ie, meningoencephalitis, sepsis, and non-septic illness) with those of age and gender matched healthy controls. Salivary samples were collected at time of awaking, 30 min and 12 h after awaking, on two consecutive weekdays. Results: Recruitment of participants is currently ongoing. Preliminary data from 19 children (10 males, 9 females) admitted to PICU (mean age: 10.53 years; SD 3.69) has been analysed and compared with data from 14 healthy controls (10 males, 4 females; mean age 11.93, SD 2.84). No differences between the whole PICU group and healthy controls were found on awaking or 30 min cortisol levels nor on any of the sAA measures, but there was a trend for lower evening cortisol in the PICU participants (p=.058). The comparison between PICU subgroups and healthy controls showed statistically significant lower evening cortisol levels in the non-septic illness subgroup (n=7) only (p=0.007). Conclusion: Our preliminary findings suggest anomalies in cortisol regulation following admission to PICU. These findings need confirmation in a larger sample and their relevance for neurocognitive and emotional function require clarification.